Crystals from the sea a look at salt - Stone, A. Harris; Ingmanson, Dale E.; Plasencia, Peter P. (Englewood Cliffs, N.J. Prentice-Hall, 1969)
Gives instructions for simple experiments which demonstrate the various physical and chemical characteristics of salt.
Keywords: Salt -- Juvenile literature; Salt